Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

BEST RESPONSE WILL GET A MEDAL AND A FAN For the following system, if you isolated y in the first equation to use the Substitution Method, what expression would you substitute into the second equation? 4x − y = 8 2x + 3y = 9 8 − 4x 8 + 4x −8 + 4x −8 − 4x

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
help please
4x-y=8 Add y both sides wht do u gt ?
i dont understand

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Adding y both sides 4x-y+y=8+y 4x=8+y
Gt it till right here ?
oh yes
what do i do next
Actually what you are being asked to do is find an expression for y in terms of x, and substitute that into the second equation. So if your two equations are 4x − y = 8 2x + 3y = 9 Then from the first equation we have that -y = 8 - 4x hence y = -8 + 4x or y= 4x - 8 This is the expression you would substitute into the second equation, as in 2x + 3y = 9 thus 2x + 3(4x - 8) = 9 Note the the question is NOT asking you to solve the equations. It is just asking you to find an expression for y from the first of each pair of equations which you would substitute into the second equation.
Oh okay
so it's -8-4x?
hello
No 4x - y = 8 Hence -y = 8 - 4x and thus y = -(8-4x) y = 4x - 8
but what if that isnt one of the choices
But it IS one of the choices.
4x - 8 is equal to exactly one of these expressions: 8 − 4x 8 + 4x −8 + 4x −8 − 4x
which one?
8-4x?
4x - 8 Can it be 8 - 4x, I don't think so, because if it were then 4x - 8 = 8 - 4x = -(4x - 8)
Remember that a + b = b + a. This is called the commutative property of addition. Hence 4x - 8 = -8 + 4x

Not the answer you are looking for?

Search for more explanations.

Ask your own question